Predicting Life Satisfaction Based On Spiritual Intelligence and Psychological Capital in Older People - Asghar Jafari; Fatemeh Hesampour (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Old age is a significant period in life and due to the development of science and improvement in health conditions, the number of elderly people is increasing in various societies. To promote the adjustment of the elderly population in the society, it is necessary to pay attention to their life satisfaction. Therefore, the present study aimed at predicting life satisfaction of elderly people based on their spiritual intelligence and psychological capital. Methods & Materials The research method is descriptive and correlational. The study population comprised 180 people residing in elderly homes in Kashan City, Iran. Of them, 123 subjects were selected based on the Morgan table and simple random sampling. The data were collected using the questionnaires of life satisfaction, spiritual intelligence, and psychological capital, then e obtained data were analyzed by Pearson correlation and multiple regression tests. Results The mean (SD) values of age, perception and connection to universe, spiritual life, self-efficacy, hopefulness, resiliency, optimism and life satisfaction were 70 (2.5) years, 62.18 (7.14), 51.11 (6.75), 24.14 (4.14), 24.33 (4.11), 21.08 (4.38), 28.33(5.04), and 21.71 (2.75), respectively. The results showed that the components of spiritual intelligence and psychological capital significantly predicted the level of life satisfaction in the elderly (P<0.01) and the perception and connection to the universe and hopefulness predicted more changes in life satisfaction among the elderly (P<0.01). Conclusion The results suggest that the components of spiritual intelligence and psychological capital can partially predict life satisfaction in the elderly. Therefore, in order to increase the level of life satisfaction in them, it is necessary to promote their spiritual intelligence and psychological capital.